Stigma related to podoconiosis in Ethiopia: a systematic review - Abiso, Temesgen Lera; Kerbo, Amene Abebe; Woticha, Eskinder Wolka; Koyira, Mengistu Meskele (Frontiers in Tropical Diseases, 2024)
BackgroundPodoconiosis, one of the neglected tropical diseases (NTDs), affects barefoot people in impoverished regions and contributes to poverty by having negative impacts on economic output, education, and disability. Podoconiosis has enormous social, psychological, and economic implications for the affected individuals. Social stigmatization of people with the disease is widespread, and patients are restricted from schools, local meetings, mosques, and churches and not allowed to marry into unaffected families. Therefore, this study aimed to systematically review the stigma related to podoconiosis in Ethiopia.MethodsThe Preferred Items for Systematic Reviews and Meta-analysis (PRISMA-2020) guidelines were followed. PubMed/Medline, Scopus, Web of Science, Google Scholar, and Google databases were searched. Articles published in the English language from inception to 2023 were included. Data were extracted by using a pre-prepared Excel sheet, and a narrative synthesis of the findings was done. This review was registered in the PROSPERO International Prospective Register of Systematic Reviews with registration number CRD42024510091.ResultsA total of 19 studies were included in this systematic review. This systematic review identified different types of stigmas reported from individuals with podoconiosis. The types of stigmas identified were enacted, felt, and internalized stigma and social stigmas, including exclusion from different social occurrences such as idir, meetings, funerals, and churches/mosques. Stigma also prevented patients with podoconiosis from visiting health institutions for the treatment of the disease and using health services for other cases.ConclusionsStigma among podoconiosis patients is widely distributed in Ethiopia. Different types of stigmas were identified among the patients. Extensive work needs to be done to prevent the disease and stigma. Strengthening works on community awareness about the disease help to ensure that it does not get transmitted from affected individuals to others.Systematic review registrationPROSPERO, identifier CRD42024510091.